2020
DOI: 10.1002/cmdc.202000533
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Prediction of Antimicrobial Efficacy for Hydrogen Bonded, Self‐Associating Amphiphiles

Abstract: Herein we report 50 structurally related supramolecular selfassociating amphiphilic (SSA) salts and related compounds. These SSAs are shown to act as antimicrobial agents, active against model Gram-positive (methicillin-resistant Staphylococcus aureus) and/or Gram-negative (Escherichia coli) bacteria of clinical interest. Through a combination of solution-state, gasphase, solid-state and in silico measurements, we determine 14 different physicochemical parameters for each of these 50 structurally related compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 54 publications
4
44
0
Order By: Relevance
“…This chemical group, common to all OP CWAs, plays a significant role in both molecular surface coordination properties and reactivity. Herein, we extend our prior work, which showed that simple, low level computational modelling may be used to predict hydrogen bond mediated aggregation events 26,27 and antimicrobial activity, 28 to identify appropriate OP CWA simulants for the development of supramolecular detection technologies, complementing the recent advances made in this area for hydrolysis siumulants. 25 Here, we hypothesised that neutral hydrogen bond donating receptors 1-4 ( Fig.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…This chemical group, common to all OP CWAs, plays a significant role in both molecular surface coordination properties and reactivity. Herein, we extend our prior work, which showed that simple, low level computational modelling may be used to predict hydrogen bond mediated aggregation events 26,27 and antimicrobial activity, 28 to identify appropriate OP CWA simulants for the development of supramolecular detection technologies, complementing the recent advances made in this area for hydrolysis siumulants. 25 Here, we hypothesised that neutral hydrogen bond donating receptors 1-4 ( Fig.…”
Section: Introductionmentioning
confidence: 69%
“…The energetics of association do not depend solely on a single molecular property, and we have previously shown that the use of an exhaustive, high throughput parameter search allows the rapid identification of predictive models. 28 To enable the elucidation of further association constant predictive models using Table 3 List of parameters (P) used to produce association constant predictive models and computational method used to derive each parameter. A definition for each of these parameters can be found within the ESI (Table S46 † N/A = non-applicable.…”
Section: Exhaustive Parameter Searchmentioning
confidence: 99%
“…1). [14][15][16][17][18][19][20][21] Similar constructs developed by Faustino and co-workers have previously been shown to act as amphiphiles with enhanced surfactant properties, attributed to intermolecular hydrogen bonded self-association. 22,23 Additionally, Supuran et al have shown the promise of agents such as SSAs for development as therapeutics against Mycobacterium tuberculosis (TB).…”
Section: Introductionmentioning
confidence: 99%
“…16 Additionally, SSAs have also demonstrated antimicrobial activity against Gram-positive MRSA and Gram-negative E. coli. [14][15][16]20 This previous work has led us to hypothesise that SSA antimicrobial activity is linked to both molecular self-association and selective SSA:phospholipid complexation, resulting in molecular membrane permeation events. 15,16,25,26 Additionally, not only have we shown SSAs to arrive at the external microbial membrane as self-associated spherical aggregates, 16 but that these aggregates can incorporate small drug(like) guest species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation